Lizard assemblage from a sand dune habitat from southeastern Brazil: a niche overlap analysis - GISELE R. WINCK; FABIO HATANO; DAVOR VRCIBRADIC; MONIQUE VAN SLUYS; CARLOS F.D. ROCHA (Anais da Academia Brasileira de Ciências, 2016)
ABSTRACT Communities are structured by interactions of historical and ecological factors, which influence the use of different resources in time and space. We acquired data on time of activity, microhabitat use and diet of a lizard assemblage from a sand dune habitat in a coastal area, southeastern Brazil (Restinga de Jurubatiba). We analyzed the data of niche overlap among species in these three axes (temporal, spatial and trophic) using null models. We found a significant overlap within the trophic niche, whereas the overlap for the other axes did not differ from the expected. Based on this result, we discuss the factors acting on the structure of the local lizard community.